Phylogenomic analysis of the Neocallimastigomycota: proposal of Caecomycetaceae fam. nov., Piromycetaceae fam. nov., and emended description of the families Neocallimastigaceae and Anaeromycetaceae. Issue 2 (24th February 2023) - Hanafy, Radwa A.; Wang, Yan; Stajich, Jason E.; Pratt, Carrie J.; Youssef, Noha H.; Elshahed, Mostafa S.
Abstract : The anaerobic gut fungi (AGF) represent a coherent phylogenetic clade within the Mycota. Twenty genera have been described so far. Currently, the phylogenetic and evolutionary relationships between AGF genera remain poorly understood. Here, we utilized 52 transcriptomic datasets from 14 genera to resolve AGF inter-genus relationships using phylogenomics, and to provide a quantitative estimate (amino acid identity, AAI) for intermediate rank assignments. We identify four distinct supra-genus clades, encompassing all genera producing polyflagellated zoospores, bulbous rhizoids, the broadly circumscribed genus Piromyces, and the Anaeromyces and affiliated genera. We also identify the genus Khoyollomyces as the earliest evolving AGF genus. Concordance between phylogenomic outputs and RPB1 and D1/D2 LSU, but not RPB2, MCM7, EF1α or ITS1, phylogenies was observed. We combine phylogenomic analysis and AAI outputs with informative phenotypic traits to propose accommodating 14/20 AGF genera into four families: Caecomycetaceae fam. nov. (encompassing the genera Caecomyces and Cyllamyces ), Piromycetaceae fam. nov. (encompassing the genus Piromyces ), emend the description of the family Neocallimastigaceae to encompass the genera Neocallimastix, Orpinomyces, Pecoramyces, Feramyces, Ghazallomyces, Aestipascuomyces and Paucimyces, as well as the family Anaeromycetaceae to include the genera Oontomyces, Liebetanzomyces and Capellomyces in addition to Anaeromyces . We refrain from proposing families for the deeply branching genus Khoyollomyces and for genera with uncertain position ( Buwchfawromyces, Joblinomyces, Tahromyces, Agriosomyces and Aklioshbomyces ) pending availability of additional isolates and sequence data; and these genera are designated as 'genera incertae sedis' in the order Neocallimastigales . Our results establish an evolutionary-grounded Linnaean taxonomic framework for the AGF, provide quantitative estimates for rank assignments, and demonstrate the utility of RPB1 as an additional informative marker in Neocallimastigomycota taxonomy.